Institutionalisation Processes of Alevis in Germany - Keleş, Bülent (Journal of Alevism-Bektashism Studies, 2021)
60 years after the labour migration from Turkey to Germany, unfortunately there are not many publications in Turkey towards Alevi citizens, whom many researchers consider to be the most exposed to migration, and their efforts to exist in Germany. However, Germany stands out as the country where the struggles of Alevis to exist in the urban environment, which many researchers call “the Alevi awakening” and which started to rise with the 1990’s, first appeared. This paper analyses the German Alevi organisation process that revealed its first official corporate identity in 1987. The paper emphasizes the “idea-event connection” on the bases of the History of Islam’s Denominations. It also uses research methods from social sciences. In this context, we especially used qualitative research method in our study on the institutionalisation process of Alevis in Germany. Since we adopted the participatory observation and interview method and benefited from the experiences of the persons we interviewed, we chose the phenomenological approach of qualitive research method within the scope of our study. Thus, in this context, we conducted in-depth interviews with a significant number of the names, who initiated the Alevi institutionalisation in Germany, using semi-structured questionnaire, and we tried to document the organisation process through the information they provided. For the study, we selected corporate structures emerged for the purpose of representing in the religious sphere Alevis living in different cities in Germany, and we chose as “purposive sample” the names who have taken part in the establishment process of these institutional structures or are already in their management. While carrying out the phenomenological approach, we tried to pay maximum attention to the trust of the names that we chose as phenomenon and who played important roles in the institutionalisation of Alevis. In order to provide a trust environment, we particularly prioritized our Alevi identity. We tried to reach the correct information by comparing information and documents about the institutional process obtained from our interviewers with the stories from the memoirs as well as the information given by other interviewers.
Keywords: Alevi institutionalisation; Germany; Alevis; Alevism; dede-centred; culture-centred